Size induced magnetic phases in half doped manganite nanowires of La0.5Sr0.5MnO3: a neutron diffraction study. (27th September 2017) - Datta, Subarna; Kaushik, S D; Siruguri, V; Kumar, Amit; Yusuf, S M; Ghosh, Barnali
Abstract: We report size reduction induced modification of magnetic property leading to phase separation and its correlation with crystallographic structure in one dimensional nanostructure of manganite system (La0.5 Sr0.5 MnO3 )—which has not previously been reported. Structural study has been undertaken using synchrotron x-ray and neutron diffraction. These studies show the coexistence of crystallographic (tetragonal and orthorhombic) and magnetic phases (ferromagnetic (FM) and antiferromagnetic (AFM) respectively) below the Néel temperature (<200 K). Neutron depolarization experimentation also corroborates the neutron diffraction results. Our results demonstrate that the coexistence of the FM and AFM phases arises due to structural phase separation of tetragonal and orthorhombic phases. In contrast, bulk La0.5 Sr0.5 MnO3, showing FM (tetragonal phase) throughout the measured temperatures (6–300 K), does not show any phase separation. Our study will provide in-depth understanding of the underlying physics and basic mechanism of size induced phase separation in nanowires, and the role of crystal structure in stabilizing a specific ground state of these manganite nanowires.